2022
DOI: 10.33235/wcet.42.4.14-30
|View full text |Cite
|
Sign up to set email alerts
|

A risk factor model for peristomal skin complications

Abstract: For people living with an ostomy, leakage and peristomal skin complications (PSC) are common issues that often appear together. Better means of preventing these issues could improve the quality of life of these patients. The purpose of the research presented here was to identify and build a model of risk factors for PSC.Risk factors were identified via discussion sessions with Coloplast's internal ostomy care experts, the Coloplast Skin Expert Panel, the Global Coloplast Ostomy Forum (COF), and 18 national COF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The Modified Delphi Process resulted in a strong consensus around the importance of maintaining peristomal integrity and the risk factors that must be considered in the prevention of PSC. The evidence identified in the literature review 13 and the experiential evidence gathered through the surveys and the facilitated dialogues led to the development and ratification of the PSC risk factor model (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Modified Delphi Process resulted in a strong consensus around the importance of maintaining peristomal integrity and the risk factors that must be considered in the prevention of PSC. The evidence identified in the literature review 13 and the experiential evidence gathered through the surveys and the facilitated dialogues led to the development and ratification of the PSC risk factor model (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Claessens et al 12 reported that 91% of people with an ostomy surveyed said they worry about leakage, 40% said they wake up at night because of their ostomy, 33% said that they limit their physical and social activities and 12% indicated that they socially isolate. However, while the literature supports a direct correlation between quality of life and PSC, understanding the risks to peristomal skin health are not well documented 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation